Fortress Russia conspiracy theories in post-Soviet Russia - Yablokov, Ilya (Polity Press, 2018)
The post-Soviet period explores how, in the new millennium, the image of the 'dangerous, conspiring West' provides national unity and has legitimised Russia's turn to authoritarianism under Putin. It will be of great interest to anyone who wishes to understand Russia's role in the world today.